A Law for the Social Sciences Regarding Us Human Beings. (July 2016) - Cardao-Pito, Tiago
This article proposes a feasible law for the social sciences asserting that we human beings are not commodities, assets, capital or resources. Mainstream economics and Marxism describe human participation in economic and societal production through a human-commodity framework. Intangible flow theory aims to replace that framework and interrelated conjectures as human capital, human assets and human resources. This theory is not exclusively applicable to capitalist/market organization forms. It suggests that (a) commodities are physical goods, and exhibit known characteristics differentiating them from human-related flows as service or knowledge flows; (b) human work has properties that make it akin to quasi-service production; (c) humans are not commodities, capital, assets or resources; (d) machines can obtain the skills necessary to replace human work or perform novel tasks when previously intangible dimensions are turned tangible (tangibilization); and (e) cash-flows generated or saved by those machines tend to flow to human beings who own or control them. According to this theory, greater attention must be paid to flows of economic material elements that display a relevant degree of empirical precision (e.g., cash and physical goods flows). JEL: A1, B1, B2, B4, B5